FOUCAULT DAN KOMUNIKASI (TELAAH KONSTRUKSI WACANA DAN KUASA FOUCAULT DALAM LINGKUP ILMU KOMUNIKASI) - Sari Monik Agustin (Jurnal Ilmu Komunikasi, 2009)
This writing aims to introduce Foucault’s life and perspectives, especially to communication studies’ students. This writing consists of Foucault’s background, his idea, research based on it and critiques. Foucault’s life background has influenced many of his ideas, and this writing focuses on his perspectives of Power and Discourse. This writing also gives example to students on how to use Foucault’s idea in Communication field. One of the examples is research about the construction of normative body discourse to the self-concept of single and fat adult women. The research used Michel Foucault’s power relations and discourses, Berger-Luckman’s construction of social reality, and Cooley-Mead’s symbolic interactionism as the framework. The research had succeeded to categorize discourses and self-concepts as the conclusion of the con- struction of normative body discourse to the self-concept of single and fat adult women in Jakarta. As an ending part, this writing shows critiques of Foucault’s idea from other social theorists.